P-002 The Two Catheter Technique in Comparison to Stent-Assisted Coil Embolisation in the Endovascular Treatment of Intracranial Aneurysms. (14th July 2013) - Gaughen, J; Durst, C; Geraghty, S; DeMartini, N; Kreitel, D; Medel, R; Patrie, J; Jensen, M; Evans, A
Abstract : Introduction/Purpose: Scientific data currently demonstrates the superiority of coil embolisation over open surgical clipping for the treatment of intracranial aneurysms. As technological advancements continue within the endovascular arena, these endovascular outcomes are expected to improve. Adjunct measures such as balloon remodelling and stent-assistance are increasing the percentage of intracranial aneurysms that can be treated endovascularly, and data is actively being collected to better understand the safety and efficacy of these adjunct modalities. The two catheter technique of endovascular aneurysm treatment is a competitive treatment strategies to these adjunct methods that involves the simultaneous deployment of coils through two catheters placed in an intracranial aneurysm sac for treatment of wide-necked aneurysms. This study evaluates the safety and efficacy of the two catheter technique in comparison to stent-assisted coil embolisation in the endovascular treatment of intracranial aneurysms. Methods: A retrospective chart review identified 110 consecutive aneurysms which were embolised using the two catheter technique and 101 consecutive aneurysms treated by stent assisted coil embolisation. Patient demographics, details of treatments, effects of treatments, results of follow up procedures, and complications were recorded. Comparison of the two catheter and stent groups was performed using Fisher's exact test. Results: The technical success rates between the two-catheter and stent groups were similar at 91% and 95%, respectively. Primary occlusion rates were also similar at 14% for the two-catheter technique and 16% for stent-assisted embolisation. An additional 38% and 39%, respectively, had only neck remnants. As might be expected, recanalisation rates were slightly higher in the two catheter group, 25% vs 16%, though this was not statistically significant (p=0.141). This did not result in a statistically significant increase in the number of retreatments. Permanent morbidity was lower in the two catheter group, 7% vs 11%; however, this was not statistically significant (p=0.108). Conclusion: The two catheter technique appears to be as safe and effective as stent-assisted coil embolisation in the endovascular treatment of intracranial aneurysms. Although not statistically significant, the treatment trended towards lower permanent morbidity. Disclosures: J. Gaughen: 2; C; Covidien. C. Durst: None. S. Geraghty: None. N. DeMartini: None. D. Kreitel: None. R. Medel: None. J. Patrie: None. M. Jensen: 2; C; Covidien, Microvention, Stryker. A. Evans: 2; C; Covidien, Microvention.